What Makes a Good Research Paper? Examining Differences and Similarities in Turkish and American Expectations - (:unkn) unknown (My University, 2014)
Araştırma makalelerindeki başarı bilgi toplamak ve fikirlerini ve yorumlarını sunmak kadar eğitimcinin iyi bir araştırmadan ne anladığıyla ve iyi bir araştırma makalesinin nasıl olması gerektiğiyle ilgili görüşlerini anlamakla da ilgilidir. Her eğitimcinin iyi bir araştırma makalesinin odağında ne olması gerektiğine ve bilgi, bağımsız düşünme, yapısı ve dilin kullanıma dair farklı görüşleri vardır. Üniversitelerin öğrenci ve eğitimci profillerini çeşitlendirme çabalarıyla birlikte bu farklılıklar daha da artmıştır. Bu çalışma da Türk ve Amerikan eğitimcilerin kültürel ve öğrenim geçmişlerinin, onların iyi bir araştırma makalesinden ne anladıklarını nasıl etkilediği araştırmayı amaçlamıştır. Araştırma verileri hem Türk hem Amerikan eğitimcilerle görüşme tekniği kullanılarak elde edilmiştir. Görüşmeler, farklı eğiticilerin araştırma makalelerine dair görüşlerinin ve onları değerlendirme şekillerinin çok farklı olduğunu ortaya koymuştur.

Success in a research paper is not only about gathering information and presenting your own thoughts and interpretations; equally as important understands the instructor's understanding of what the purpose of research is and what constitutes a good research paper . Individual instructors often have very different ideas about what the focus of the paper should be and what they are looking for in terms of information, independent thinking, structure, and accuracy of language. These differences become even more marked as universities seek to diversify their student bodies and teaching staff. This study aimed to explore Turkish and American instructors perceptions regarding the possible influence of their cultural and educational backgrounds on their understanding of a good research paper. The data was obtained from interviews of both Turkish and American instructors to examine the similarities and differences in expectations for research assignments. These interviews revealed some differences in how different instructors view research assignments and how they grade them.
İyi Bir Araştırma Makalesi Nasıl Olur? Türk ve Amerikan Beklenti Arasındaki Benzerlikler ve Farklar
Keywords: Eğitim, Eğitim Araştırmaları